Spalling behaviour of concrete made with recycled concrete aggregates. (15th August 2022) - Fernandes, Bruno; Carré, Hélène; Mindeguia, Jean-Christophe; Perlot, Céline; La Borderie, Christian
Abstract: Concrete made with recycled concrete aggregates (RCA) presents particular properties that may lead to a specific behaviour under fire conditions, including the spalling risk. The spalling sensitivity of concrete made with RCA was evaluated through a campaign conducted in three concrete series: reference, direct replacement, and strength-based replacement. The last was designed to have the same performance as concrete made with natural aggregates (NA). Samples with different replacement rates of recycled coarse aggregates (0 %, 10 %, 20 %, 40 %, and 100 %) were exposed to the standard fire curve (ISO 834-1) with constant uniaxial loading (2.5 and 5 MPa). During the tests, the furnace temperature and spalling events were recorded. After the tests, digital photogrammetry was used to observe the spalling damage (volume and depth). Fire tests indicated that concrete made with RCA exhibited a higher spalling degree than concrete made with NA. Results also show that the replacement rate acts in different ways: in concrete with RCA replacement rates up to 40 %, the spalling damage increases, but a further increase does not lead to higher spalling. In addition, RCA changes the physical properties of concrete, which may trigger spalling, particularly water content. Highlights: The spalling sensitivity of concrete made with RCA was investigated. Digital photogrammetry was used to evaluate the damage degree of spalled specimens. For the given conditions, concrete made with RCA showed more spalling damage than concrete made with NA. The higher water content of concrete made with RCA was one of the triggering parameters for spalling.